The Usher syndrome 1C protein harmonin regulates canonical Wnt signaling - Schäfer, Jessica; Wenck, Nicole; Janik, Katharina; Linnert, Joshua; Stingl, Katarina; Kohl, Susanne; Nagel-Wolfrum, Kerstin; Wolfrum, Uwe (Frontiers in Cell and Developmental Biology, 2023)
Human Usher syndrome (USH) is the most common form of hereditary combined deaf-blindness. USH is a complex genetic disorder, and the pathomechanisms underlying the disease are far from being understood, especially in the eye and retina. The USH1C gene encodes the scaffold protein harmonin which organizes protein networks due to binary interactions with other proteins, such as all USH proteins. Interestingly, only the retina and inner ear show a disease-related phenotype, although USH1C/harmonin is almost ubiquitously expressed in the human body and upregulated in colorectal cancer. We show that harmonin binds to β-catenin, the key effector of the canonical Wnt (cWnt) signaling pathway. We also demonstrate the interaction of the scaffold protein USH1C/harmonin with the stabilized acetylated β-catenin, especially in nuclei. In HEK293T cells, overexpression of USH1C/harmonin significantly reduced cWnt signaling, but a USH1C-R31* mutated form did not. Concordantly, we observed an increase in cWnt signaling in dermal fibroblasts derived from an USH1CR31*/R80Pfs*69 patient compared with healthy donor cells. RNAseq analysis reveals that both the expression of genes related to the cWnt signaling pathway and cWnt target genes were significantly altered in USH1C patient-derived fibroblasts compared to healthy donor cells. Finally, we show that the altered cWnt signaling was reverted in USH1C patient fibroblast cells by the application of Ataluren, a small molecule suitable to induce translational read-through of nonsense mutations, hereby restoring some USH1C expression. Our results demonstrate a cWnt signaling phenotype in USH establishing USH1C/harmonin as a suppressor of the cWnt/β-catenin pathway.